2019
DOI: 10.1177/1757177419879996
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the World Health Organization’s fifth moment for hand hygiene: Infection prevention in the operating room

Abstract: Background: The World Health Organization have designed the fifth of their ‘5 moments’ for hand hygiene to account for microbial transfer from patients to equipment in a narrow area around that patient, known as the patient zone. The study was prompted by emerging local confusion about application of the patient zone in the operating room (OR). Aim/Objectives: In two phases, we aimed to create a ‘5 moments’ style poster displaying an OR patient zone: phase 1, quantify equipment, in direct contact with the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Application of the IPC guidelines developed by the Centre for Disease Control for reducing HAI form the basis for preventing transmission of micro-organisms within a hospital facility [1, 10]. Although the guidelines were not on site, participants for this study reported that they heard about IPC guidelines during their professional training and were familiar with them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of the IPC guidelines developed by the Centre for Disease Control for reducing HAI form the basis for preventing transmission of micro-organisms within a hospital facility [1, 10]. Although the guidelines were not on site, participants for this study reported that they heard about IPC guidelines during their professional training and were familiar with them.…”
Section: Discussionmentioning
confidence: 99%
“…Application of the IPC guidelines developed by the Centre for Disease Control for reducing HAI form the basis for preventing transmission of micro-organisms within a hospital facility [1,10].…”
Section: Existing Guidelines On Selected Infection Prevention and Con...mentioning
confidence: 99%
“…Im Rahmen von Fortbildungen ist es wichtig, die Mitarbeiter bezüglich der Entwicklung eines Bewusstseins für Infektionsprozesse zu unterstützen, denn nur, wenn dieses Bewusstsein vorhanden ist, ergreifen sie selbstständig spezifische Schritte, um eine Infektion zu verhindern. Zum einen sind dazu Händehygienefortbildungen erforderlich, da das vermittelte Wissen das individuelle Verhalten der Mitarbeiter maßgeblich beeinflusst und existierende Wissenslücken geschlossen werden können [ 14 ]. Zum anderen kann eine Verhaltensänderung aber auch durch ein Feedback zur HHC und zu den Infektionsraten unterstützt werden.…”
Section: Diskussionunclassified
“…Most ophthalmic operations are not general anesthesia, patients can continue to wear surgical masks during the operation; if it is general anesthesia, it is recommended to place a disposable filter between the tracheal intubation and the breathing circuit to reduce the pollution of the breathing circuit, the anesthesia machine Strictly disinfect after use ( 20 ).…”
Section: Outpatient Management Planmentioning
confidence: 99%